Optimization of Production Factors in Organic Rice Farming in Sleman Regency, Yogyakarta - Triyono; Al Uth’aini Toha; Nur Mila Amalia; Fauzi bin Kamrudin Mohd; Mamnuah (E3S Web of Conferences, 2023)
Rice is a promising commodity to be cultivated organically but still requires attention in the optimal use of production factors to achieve maximum results. The control of production factors is still limited in number by farmers while high production and profits are expected. The purpose of this study was to determine the factors of production, costs, and profits and to analyse the allocation of optimal use of production factors to achieve maximum profit in organic rice farming in Sleman Regency. Farming data were obtained from 70 organic rice farmers and analysed using linear programming methods. The results show that the use of production factors during the two growing seasons showed that the average land use was 1,555 m2, the use of seeds was not in accordance with the recommendations, more workers used outside the family, dominant farmers used solid organic fertilizers and liquid organic fertilizers as support. The average total cost incurred by farmers is IDR. 2,540,263 and IDR. 2,622,826 with an average profit of IDR. 2,414,237 and IDR. 2,181,8888. Optimization analysis shows that the use of land production factor costs is optimal, while the labour cost, seeds, solid organic fertilizers, and liquid organic fertilizers is still not optimal.